Co-creating corporate brand identity with online brand communities: stakeholder and process-oriented perspectives - Essamri, Azzouz (2019)
Contrary to the traditional conceptualisation of corporate brand identity as a static concept that is defined and articulated through an internally strategic driven process, the contemporary logic of branding characterises brand identity as dynamic and co-created through continuous interactions with multiple stakeholders in social contexts. Despite recent work on how brand communities and individuals contribute towards brand identity construction, our understanding of the iterative and reciprocal processes of stakeholder interaction involved in the co-creation of brand identity is still under-developed. Current research in brand management literature does not provide systematic insights into processes and activities involved in the formation of brand identity. The aim of this thesis is to systematically study the co-creation of corporate brand identity from stakeholder- and process-oriented perspectives. It focuses on management-led processes as well as on brand identity co-creation activities of the brand community constituting part of the wider process of a socially constructed brand identity. Applying an interpretive case study approach involving in-depth interviews with senior executives of an iconic luxury automotive brand and a netnography of its online brand community, this thesis develops a process model of corporate brand identity co-creation, comprising three management-led processes (i.e., nurturing brand passion, bridging corporate brand identity meanings ,and partnering) and the unfolding activities through which management contributes to the wider process of corporate brand identity formation with community members and other stakeholders. By highlighting the interlinked and recursive nature of these processes and activities in the resulting model, the study offers a deeper understanding of the ways in which managers are involved in co-creating corporate brand identity. The findings provide empirical evidence for the important role of managers acting as collaborators, listeners, and co-authors as well as the importance of corporate culture in the process of brand identity co-creation. Given the notion in recent research that various stakeholders can contribute to the construction of brand identity, it is imperative to take a comprehensive look into how each stakeholder contributes to this process. On the basis of data from a netnographic study of the online brand community, the thesis identifies co-creation activities through which the brand community contributes to the co-creation of brand identity and shows how brand identity meanings are enacted and negotiated within the brand community and amplified to a broader audience. This also shows that brand identity is out of managers’ control and helps understand how the brand identity, as a complex social phenomenon, develops among a multitude of enacted identities. Taken together, this thesis conceives of brand identity as a constellation of meanings and contributes to the radical shift in branding literature that highlights the dynamic, reciprocal and iterative nature of the brand identity concept. In this regard, the overall findings of this thesis contribute to brand identity theory, brand community theory, and co-creation theory.